Pregled publiciranja izbranih bibliografskih enot visokošolskih učiteljev strokovnih predmetov zdravstvene nege - Bregar, Branko (Obzornik zdravstvene nege, 2020)
Introduction: The quality of study programmes is related to the academic skills of higher education lecturers. The aim of the research was to examine the publications of lecturers of professional subjects at higher education institutions offering nursing study programmes in Slovenia. Method: Publicly available data of publications by 76 lectures of 12 professional subjects at higher education institutions offering nursing study programmes were retrospectively reviewed for the period from 2010 to 2015. Data are presented with descriptive statistics. Results: 4337 units of publication were published in the period, per one lecturer 57.32 (s = 59.05). The most units were mentoring diploma theses (n = 2928, 67.30%), the lowest number of units comprised the publication of original scientific articles (n = 268, 6.21%), and there were even fewer review articles published (n = 46, 1.10 %). There are significant differences in all published units between faculties (x2(2) = 14.272, p = 0.027), in mentoring (x2(2) = 16.767, p = 0.010), review articles (x2(2) = 28.442, p < 0.001) and editorial units (x2(2) = 17.870, p = 0.007). Discussion and conclusion: The holders of professional nursing subjects engage in various activities in the field of publishing bibliographic units. Higher education institutions should encourage higher education lecturers to publish and thus promote their professional and scientific development. Publication of scientific bibliographic units could be added as one of the criteria for appointment to the titles of higher education teachers including the title of lecturer.
Keywords: faculties; fakultete; health care; higher education; kakovost; medicinske sestre; nurses; quality; visoko šolstvo; zdravstvo